Draft Annual Plan 2003-04 Volume - II Government of Karnataka - Planning Commission (Planning Commission, 2003)
Draft Annual Plan 2003-04 - Proposed Outlays - Outlay by Major Heads of Development Draft Annual Plan 2003-04 Proposed Outlay - Scheme-wise allocation Physical Targets and Achievements A Draft Annual Plan (2003-04) Proposals for Spillover and Ongoing Programmes Draft Annual Plan (2003-04) Proposals for Maximising Benefits of Completed Programmes Draft Annual Plan (2003-04) - Proposals for Programmes I Projects - New Schemes Summary Statement Draft Annual Plan (2003-04) Proposals for Programmes/Projects Statements regarding Externally Aided Projects Draft Annual Plan (2003-04) - Outlays - By heads of Development - for District Plans Centrally Sponsored Schemes.
Government of Karnataka, Planning, Statistics and Science and Technology Department